Extraction of charges from beneath the surface of liquid hydrogen - Levchenko, A.A.; Mezhov-Deglin, L.P. (Физика низких температур, 1996)
Experimental results are presented which confirm the existence of electron bubbles in liquid hydrogen. The effective values of the barrier preventing the glectron to escape from the liquid into the gas and the electron bubble radius are estimated to be 350 ± 70 К and 10 A, respectively. The experiments show that β-radiation gives rise to both the electron bubbles and the negatively and positively charged clusters (snowballs) in liquid hydrogen. Quasi-periodic oscillations of the charged surface and extraction of ~ 10⁸ charges during a pulse have been observed at electric fields higher than some critical value ~ 10³ V/cm.